Effect of educational intervention on the intention to provide family-centered care among selected hospitals’ paediatric nurses in Tehran, Iran - Rostami, Forouzan (2015)
Family-centred care (FCC), which has become the cornerstone for paediatric nursing practice, supports the trust of child and family health. Families are recognised as an essential part of a specialised childcare during illness and they are expected to be skilful in childcare. In Iran, studies have shown that for parents to be involved in the care for hospitalized children there are obstacles that need to be discussed and investigated. There are huge gaps between effective health services and real world practice. Moreover, there is no common agreement between health care workers about provision of FCC in Iran. Hence, The main goal of this study was to examine, the effect of an educational intervention on the intention to provide family-centred care among paediatric nurses in Iran. The research design of the study was quasi-experimental. A total of 200 paediatric nurses in two groups (100 intervention and 100 control), aged 25-55 from hospitals affiliated to Shahid Beheshti University (1 control and 3 intervention hospitals) in Tehran, Iran. Four hospitals were selected randomly based on the purpose of choosing hospitals that have paediatric wards for two groups (intervention and control groups). Proportionate sampling technique was employed. The educational intervention (twoday education classes) was conducted during the first month, and the effects on dependent variables of the study were assessed almost immediately after the intervention and three months later. In the intervention group, nurses were provided with presentations and internet-based education concerning FCC, in addition to booklets and pamphlets. The control group received one educational pamphlet about nutrition in children. To evaluate the effect of the intervention, data were collected at baseline, immediately following, and three months after the intervention, for both groups. Researcher-guided self-administered questionnaires were given to both groups prior to the intervention, immediately after the intervention, and three months after the intervention. Descriptive and multivariate statistics (repeated measures ANOVA) were used for analysing the data. The mean age of participants was 36.1 years (SD = 9.1), and they were female (100%) without any specific training about FCC (93.8%). After the intervention, there was a significant increase in the mean score of attitude [mean i.e. M (pre) = 3.35%, M (post) = 3.97, P < 0.001)], subjective norms [M (pre) = 3.72, M (post) = 4.21, P < 0.001)], perceived behaviour control [M (pre) = 3.36, M (post) =3.75, P < 0.001)], and intention [M (pre) = 3.56, M (post) = 4.37, P < 0.001)], over the 3-month follow-up in the intervention group. The data provided preliminary support for effectiveness of the Theory of Planned Behaviour in producing constructs that significantly increased attitude, subjective norms, perceived behaviour control, and intention towards FCC in the intervention group. The multiple linear regression models showed that changes in attitude, subjective norms, and perceived behaviour control scores were the predictors of the change in intention towards FCC. The most significant predictor was attitude (β = 0.393, t =5.914, p < 0.01), followed by perceived behaviour control (β = 0.320, t = 4.815, p < 0.01) and subjective norms (β = 0.172, t = 2.184, p < 0.01). The last model was related to the follow-up test and the results showed the same pattern where attitude still showed the highest impact on intention (β = 0.319, t = 4.889, p < 0.01) followed by perceived behaviour control (β = 0.309, t = 5.174, p < 0.01) and subjective norms (β =0.264, t = 4.138, p < 0.01). The results provide evidence in support of the thesis that education can enhance attitude, subjective norms, perceived behaviour control, and intention to provide FCC within an educated group such as paediatric nurses, who represent a large portion of educated nurses in Iran. The study suggests that health care professionals can focus especially on teaching young nurses and parents to promote paediatric health through FCC.